Capacity building in clinical and molecular characterization of rare neurodegenerative diseases through the development of a local register and improved use of bioinformatics data analysis in Martinique - Anna-Gaelle; Jacqueline Véronique-Baudin; Yannis Duffourd; Jocelyn Inamo; Cyril Goizet; Rémi Bellance; Juliette Smith-Ravin (Inishmore Laser Scientific Publishing Ltd, 2020)
Neurodegenerative diseases (NDs) are very polymorphic and affect people of all ages. They concern both rare diseases and more common diseases. Improving knowledge of NDs in the French Caribbean region requires special attention because of the unique environmental and genetic background of its populations. In Martinique, there is a huge need for scientific research on rare NDs. While epidemiological and clinical research has increased over the past decade in the French West Indies, there is still little or no data on the genetics of NDs in these regions. The advent of Next Generation Sequencing (NGS) on a global scale has the potential to make a difference in this field, provided that technological and analytical knowledge, based on bioinformatics, is available in Martinique. Caribbean Reference Center for rare neuromuscular and neurological disorders (CERCA), is a reference center for diagnosis, health care and treatment of rare NDs. It supports our capacity building project in the clinical characterization of rare NDs with motor impairment, with or without dementia. In collaboration with CERCA, we designed a two-step pilot study, consisting of: 1) the creation of a clinical and biological database to select informative cases, and 2) to screen them by whole exome sequencing. This innovative approach involves: 1) mobilization of medical and clinical knowledge for the characterization of rare ND, with the support of a register of experts, and 2) expertise in molecular biology, molecular pathways and bioinformatics. This preliminary study confirms the need to consider our French West Indian population in these specificities. It reveals the effectiveness of a well-tune database for identifying pathogenic variants in a cohort of French West Indian patients with presumed genetic NDs, associated with motor impairment with or without dementia. It is a proof of concept that the creation of a register of NDs and the mastery of NGS technique, can provide additional expertise in research and patient management in the Caribbean. The continuation of this capacity building project should increase CERCA's skills and outreach. Such an initiative is clearly innovative for the region and would bring the Caribbean, Latin America and North America communities together, around the subject.